2018
DOI: 10.1016/j.ypmed.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Parenting practices and overweight status of junior high school students in China: A nationally representative study of 19,487 students from 112 schools

Abstract: The study aimed to examine the level of parental responsiveness and demandingness for junior high students in China and its association with child weight status; assess if it differs by student socio-demographic characteristics; and to test the association between parenting and child physical activity. Nationally representative survey data collected from 19,487 students in 112 middle schools across China in 2013-2014 academic year were analyzed in 2016. Children's anthropometrics and perceptions of parenting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…There is a relationship between parenting and obesity in children. Children who are in foster care with parenting style authoritarian will tend to experience obesity is 1.1 to 1.4 times that of the children in foster care with the style of parenting authoritative [12]. Several studies have shown that authoritative parenting is the least risky parenting model for a child's weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a relationship between parenting and obesity in children. Children who are in foster care with parenting style authoritarian will tend to experience obesity is 1.1 to 1.4 times that of the children in foster care with the style of parenting authoritative [12]. Several studies have shown that authoritative parenting is the least risky parenting model for a child's weight.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excessive attention and involvement from parents can result in a higher risk of obesity and obesity among their children due to increased mental stress [18]. In addition, the relationship between a permissive parenting style and obesity puts children at a higher risk for being overweight or obese with [12] studies that show a positive relationship between permissive parenting style and child BMI [14]. When children are introduced to solid foods, they tend to like foods that are sweet and salty, calorie-dense, and reject new foods [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific details with regard to the implementation of the survey can be found in the literature. [ 23 ] In this study, seventh grade students with normal vision were selected at baseline as the research object. At the same time, data were selected from the baseline wave (the school year 2013–2014) and the third survey wave (in 2015–2016).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected through in-person interviews. A total of 10,279 seventh-grade students were randomly selected for follow-up surveys (29).…”
Section: Study Populationmentioning
confidence: 99%